2020
DOI: 10.1002/alz.12096
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D intake is associated with dementia risk in the Washington Heights‐Inwood Columbia Aging Project (WHICAP)

Abstract: Introduction: Low vitamin D intake and low vitamin D circulating levels have been associated with increased risk for dementia. We aimed to examine the association between vitamin D intake and dementia in a multiethnic cohort. Methods: A longitudinal study of 1759 non-demented older (≥65 years) participants of the Washington Heights-Inwood Columbia Aging Project with follow-up visits and completed a food frequency questionnaire. Dementia was diagnosed by consensus using Diagnostic and Statistical Manual of Ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
3
18
0
1
Order By: Relevance
“…These conflicting results may be due to different methods used, sex differences, and variations in the hormonal response of target tissue contributing to variations in lipid control and gene activation/inactivation. This interventional study found a significant elevation in levels of apo-CIII and apo-E after total adjustment of vitamin D levels which is in line with interventional studies that found a significant link between apo-E and vitamin D intake from food sources [48].The rise of these apolipoproteins in this interventional study suggests the positive modulation of vitamin D on the cardiometabolic factors. The marked increase in apo-CIII with vitamin D supplementation because of the atherogenic properties of apo-CIII appears controversial, but it must be looked at considering the fact that apo-CIII is readily exchangeable between triglyceride-rich lipoprotein and HDL systems [23].…”
Section: Discussionsupporting
confidence: 88%
“…These conflicting results may be due to different methods used, sex differences, and variations in the hormonal response of target tissue contributing to variations in lipid control and gene activation/inactivation. This interventional study found a significant elevation in levels of apo-CIII and apo-E after total adjustment of vitamin D levels which is in line with interventional studies that found a significant link between apo-E and vitamin D intake from food sources [48].The rise of these apolipoproteins in this interventional study suggests the positive modulation of vitamin D on the cardiometabolic factors. The marked increase in apo-CIII with vitamin D supplementation because of the atherogenic properties of apo-CIII appears controversial, but it must be looked at considering the fact that apo-CIII is readily exchangeable between triglyceride-rich lipoprotein and HDL systems [23].…”
Section: Discussionsupporting
confidence: 88%
“…The inclusion criteria of participants are as follows: (1) participants aged 50–70 years; (2) participants with cognitive decline in memory or other cognitive domains at least for 3 months, and was diagnosed with mild cognitive impairment (cognitive decline in one or more cognitive domains and is insufficient to affect the independence of life) according to the “Chinese Diagnosis and Treatment Guidelines for Cognitive Dysfunction Related to Cerebral Small Vascular Disease (2019)” [ 16 ]; (3) participants with the Montreal Cognitive Assessment (MOCA) score<26 (does not meet the diagnostic criteria of dementia according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition [ 17 ]) and a clinical dementia rating scale (CDR) score of 0.5 points [ 18 ]; (4) head computerized tomography or magnetic resonance imaging showed recent small subcortical infarcts, lacunes, white matter hyperintensities (WMHs), enlarged perivascular spaces, and microbleeds, and according to the “Chinese Diagnosis and Treatment Guidelines for Cognitive Dysfunction Related to Cerebral Small Vascular Disease (2019)” and “Consensus on Diagnosis and Treatment of Cerebral Small Vascular Disease in China (2015)” [ 19 ] (more than 2 lacunar infarcts outside the brain stem, Fazekas score ≥ 2 and number of cerebral micro hemorrhage ≥ 3); and (5) participants with signed informed consent for trial participation.…”
Section: Methodsmentioning
confidence: 99%
“…Randomized clinical trials testing folic acid supplementation in the elderly revealed the positive effect of maintaining cognitive ability [ 80 ]. Vitamin D deficiency, defined as serum vitamin D <10 ng/mL, was shown to be hazardous for AD according to several cohort studies [ 81 ], and Zhao et al conducted a prospective cohort study that verified that high vitamin D supplementation is protective against dementia [ 82 ]. Omega-3 fatty acids from seafood is another component found to be beneficial by inhibiting cognitive decline.…”
Section: Diet and Apoementioning
confidence: 99%